Existência e unicidade de solução global para um modelo termoelástico com domínio ilimitado - Anjos, Luis Jorge Souza dos (2023)
The main objective of this dissertation is to demonstrate the existence of a global solution for a system of partial differential equations of the hyperbolic type. The equation studied is a formulation of the heat equation following the model proposed by Cataneo. For the solution of the system we use the theory of semigroups and to show the existence of such solution we rely on results of nonlinear Functional Analysis to show the existence.